LEXICO-SEMANTIC STRUCTURE AND ITS ANALYSIS ON THE EXAMPLE OF VERBS - MUKHAYYO HASANOVNA DAVLATOVA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The lexical system and its subdivisions are the lexical levels that are separated at this stage into two major groups - independent and non-independent words. This division is based on privacy, and the sign of opposition is "spiritual and functional independence." In lexicology, language is studied as a system of lexical richness, because this richness is not a simple, mechanical sum of words and phrases, but a system of units and elements.